Effect of Selected Nanospheres on the Mechanical Strength of Lime-Stabilized High-Plasticity Clay Soils. (30th April 2019) - Ghorbani, Ali; Hasanzadehshooiili, Hadi; Mohammadi, Mostafa; Sianati, Fariborz; Salimi, Mahdi; Sadowski, Lukasz; Szymanowski, Jacek
Abstract : The proper design of protective structures may start from improving the characteristics of soils. In order to obtain reasonable safety criteria, several research studies have recently been dedicated to enhancing complex civil engineering structural systems with the use of nanotechnology. Thus, the following paper investigates the effect of nanospheres, including nanosilica (nano-SiO2 ) and nano zinc oxide (nano-ZnO), on lime-stabilized high-plasticity clay soil. For this purpose, unconfined compressive strength (UCS) and California bearing ratio (CBR) tests were performed on samples. The results showed that the use of the selected nanospheres greatly increased the UCS of the samples compared to untreated soil. The UCS value of samples containing 6% lime and 1.5% nano-ZnO after 28 days of treatment increased by 5-fold compared to the UCS of untreated samples. In addition, the samples containing 6% lime and 2% nano-SiO2, with similar curing conditions, experienced a 5.3-fold increase in their UCS value compared to the untreated samples. These compounds were considered as the optimal amounts and showed the highest mechanical strength in both UCS and CBR tests. The same trend was achieved in the CBR test, in which the CBR value for the optimal mixtures containing nano-ZnO and nano-SiO2 was 14.8 and 16.6 times higher than that of high-plasticity clay soil, respectively. Finally, the results obtained from scanning electron microscopy (SEM) analysis revealed that the nanospheres caused a dense and compact matrix to form in the soil, which led to the enhancement of the mechanical strength of the treated samples.